2014
DOI: 10.1515/dx-2014-0040
|View full text |Cite
|
Sign up to set email alerts
|

Types of diagnostic errors in neurological emergencies in the emergency department

Abstract: Background: Neurological emergencies often pose diagnostic challenges for emergency physicians because these patients often present with atypical symptoms and standard imaging tests are imperfect. Misdiagnosis occurs due to a variety of errors. These can be classified as knowledge gaps, cognitive errors, and systems-based errors. The goal of this study was to describe these errors through review of quality assurance (QA) records. Methods: This was a retrospective pilot study of patients with neurological emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 30 publications
0
6
0
3
Order By: Relevance
“…Previous studies on the misdiagnosis of neurologic emergencies have described cognitive errors, knowledge gaps, and systems-based errors as contributing factors. 11,40,57,58 In a recent meta-analysis of 15,721 patients with acute cerebrovascular events, Tarnutzer et al 8 found that misdiagnosis was more frequent for patients presenting with milder, transient, and nonspecific symptoms such as headache and dizziness. These atypical presentations are more prone to cognitive biases and failed heuristics for the physician, and therefore it is important for frontline providers to be aware of them.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the misdiagnosis of neurologic emergencies have described cognitive errors, knowledge gaps, and systems-based errors as contributing factors. 11,40,57,58 In a recent meta-analysis of 15,721 patients with acute cerebrovascular events, Tarnutzer et al 8 found that misdiagnosis was more frequent for patients presenting with milder, transient, and nonspecific symptoms such as headache and dizziness. These atypical presentations are more prone to cognitive biases and failed heuristics for the physician, and therefore it is important for frontline providers to be aware of them.…”
Section: Discussionmentioning
confidence: 99%
“…Most evidence regarding DE in acutely ill patients comes from retrospective chart review or postmortem studies. [27][28][29] In this article, we explore the reliability of chart review strategies to support real-time recognition of DE risk in acutely ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…35 The proportion of DE can vary for different populations and settings, and depends on study methodology. 4,[27][28][29] Each review was estimated to take approximately 1 hour per reviewer per patient. This has obvious implications for the scalability and use of this tool outside of our acute care learning laboratory environment.…”
Section: Discussionmentioning
confidence: 99%
“…3 Literatur lain melaporkan bahwa dari seluruh kasus kegawatdaruratan neurologis, stroke merupakan penyakit yang paling sering mengalami kesalahan diagnosis yaitu sebesar 37,9%. 4 Pada studi prospektif yang dilakukan oleh Tomi dkk. dari bulan Desember 2014-April 2015 di Instalasi Gawat Darurat (IGD) rumah sakit di Yogyakarta pada pasien stroke, sebesar 98,10% dan 61,30% subjek secara berturutturut mengalami kesalahan pengobatan pada fase peresepan dan fase administrasi.…”
Section: Pendahuluanunclassified
“…Tingginya kejadian pada kelompok knowledge gap disebabkan oleh karena kurangnya edukasi mengenai penyakit yang salah didiagnosis, termasuk penyakit stroke. 4 Studi lain mengenai penyebab kesalahan diagnosis menemukan bahwa faktor kognitif berupa kecacatan dalam memori dan kurangnya pengetahuan atau kompetensi dokter termasuk ke dalam faktor dominan yang berkontribusi. 3 Survei yang dilakukan terhadap dokter Unit Gawat Darurat (UGD) di 24 rumah sakit menunjukan hal serupa, dimana kurangnya familiaritas dokter terhadap pedoman pengobatan stroke menjadi salah satu hambatan untuk mengadministrasikan tissue-Plasminogen Activator (tPA) kepada pasien stroke iskemik akut.…”
Section: Pendahuluanunclassified